Mechanical engineering software for UNITEN (MESU) - Ten Wei Peng (2023)
This report presents the designing of mechanical engineering software for UNITEN (MESU). The idea of this design was to develop learning program in spread sheet based software using Microsoft Excel and Visual Basic Advance to do various calculations for the student. This program was design to solve the problems in beam analysis of Mechanics of Material, gear analysis of Machine Design and heat conduction of Heat Transfer.